Comparative Study Through Soil Fertility Analysis on Andosol, Latosol and Podsolik Soil Types in Bogor District - Enggalmulia, Siti Hutami; Masnang, Andi; Aisyah (JURNAL AGRIMENT, 2024)
Determination of the soil type had a significant effect on production. Therefore, type of selection and cropping land is factor that must be considered properly. This study aims to determine the level of nutrition fertility such as nutrient content found in several types of soil in Bogor regency. The types that will be analyzed are Andosol Soil, Latosol Soil, and Podsolic Soil. The parameters analyzed were water content, pH, organic carbon, total Nitrogen, available content of P2O5, potential content of P2O5, potential content of K2O, cation exchange capacity, exchangeable cation, exchangeable acidity, and 3 fraction textures. The results of the analysis showed that the highest nutrient content in a row were Andosol soil, Latosol soil, and Podsolic soil. The nutrient content values ​​in Andosol soil have good content values ​​in the parameters of organic carbon, Nitrogen, available P2O5, potential P2O5, potential K2O, and Exchangeable Cations in the K+, Na+, and Mg++ values. Latosol soil has good content values ​​in the parameters of available P2O5, potential P2O5, potential K2O, and exchangeable cations in the K+ value. The content with good value found in Podzolic soil is only the P2O5 parameter available.   Keywords: Andosol, Latosol, Podsolic, soil fertility